A subtle mimicker in emergency department: Illustrated case reports of acute drug-induced dystonia. Issue 41 (October 2016) - Angelis, Maria Vittoria De; Giacomo, Roberta Di; Muzio, Antonio Di; Onofrj, Marco; Bonanni, Laura
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Movement disorder emergencies include any movement disorder which develops over hours to days, in which failure to appropriately diagnose and manage can result in patient morbidity or mortality. Movement disorder emergencies include acute dystonia: sustained or intermittent muscle contractions causing abnormal, often repetitive, movements. Acute dystonia is a serious challenge for emergency room doctors and neurologists, because of the high probability of misdiagnosis, due to the presence of several mimickers including partial seizures, meningitis, localized tetanus, serum electrolyte level abnormalities, strychnine poisoning, angioedema, malingering, catatonia, and conversion. Methods: We describe 2 examples, accompanied by videos, of acute drug-induced oro-mandibular dystonia, both subsequent to occasional haloperidol intake. Results: Management and treatment of this movement disorder are often difficult: neuroleptics withdrawal, treatment with benzodiazepines, and anticholinergics are recommended. Conclusion: Alternative treatment options are also discussed.